2002
DOI: 10.1046/j.1365-2168.2002.02186.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain from primary inguinal hernia and the effect of repair on pain

Abstract: Clinical trials are required to evaluate hernia repair in patients with an asymptomatic inguinal hernia. Results from such trials should help to determine whether repair is the treatment of choice for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
1
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 9 publications
(5 reference statements)
2
66
1
6
Order By: Relevance
“…In a recent review Nienhuijs et al reviewed 29 good quality studies from January 1996 to June 2006 with a total of 8350 patients and a mean follow up ranging from 3 to 36 months and concluded that after mesh based repairs, 11% of patients suffer chronic pain [15]; whereas in our study we have found the incidence of CGP to be 0.78%. This is considerably less than what has been reported earlier [3,4].…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In a recent review Nienhuijs et al reviewed 29 good quality studies from January 1996 to June 2006 with a total of 8350 patients and a mean follow up ranging from 3 to 36 months and concluded that after mesh based repairs, 11% of patients suffer chronic pain [15]; whereas in our study we have found the incidence of CGP to be 0.78%. This is considerably less than what has been reported earlier [3,4].…”
Section: Discussioncontrasting
confidence: 53%
“…These advances, however threaten to be offset by the disabling complication of chronic groin pain, the reported prevalence of which varies widely, with some workers reporting an incidence of almost 75.5% [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22] Başka bir çalışmada ameliyat öncesi dönemde ağrısı olmayan ve herni operasyonu geçiren kişilerin bir yıllık takipleri sonrası ağrı skorları ameliyat öncesi dönemde ağrısı olanlara göre belirgin derecede dü-şük çıkmıştır. [23] Çalışmamızda ameliyat öncesi ağ-rısı olanlarda kronik ağrı gelişimi insidansı %21.8 olarak bulunmuştur. Erken ameliyat sonrası dönem-deki akut ağrının şiddeti ile ameliyat sonrası kronik ağrı gelişmesi arasında doğru bir orantı bulunmaktadır.…”
Section: Discussionunclassified
“…The symptom of an inguinal hernia is mostly mild and a third of patients have no pain [2]. Severe complication such as strangulation is uncommon.…”
Section: Introductionmentioning
confidence: 99%